2016
DOI: 10.1186/s12979-016-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal colonization in older adults

Abstract: BackgroundLittle is known about pneumococcal carrier states in older adults. The main aim of this study was to evaluate pneumococcal colonization patterns among older adults in two centres in Milan, Italy, before the widespread use of the 13-valent pneumococcal vaccine (PCV13) in this age group, to investigate demographic and clinical features that are associated with pneumococcal colonization and to estimate the potential coverage offered by PCV13.ResultsAmong 417 adults ≥65 years old (171, 41.1 %, ≥75 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
18
2
Order By: Relevance
“…A very recent study describing S. pneumoniae colonisation in adults >65 years of age used molecular methods of detection and reported a predominance of PCV-13 serotypes within the cohort whereas this study revealed a predominance of NVT serotypes within the cohort. 24 The different findings between this study and that of Esposito et al (2016) could be due to regional variation and the lack of molecular detection methods used in this study. A factor that may be negatively impacting on the recovery of S. pneumoniae from the study volunteers could be the high rate of antibiotic use in this patient group; patients reported high antibiotic use between visits with the median number of courses of antibiotics prescribed in the period between visits ranging from one in the spring to two in the autumn.…”
Section: Discussioncontrasting
confidence: 76%
“…A very recent study describing S. pneumoniae colonisation in adults >65 years of age used molecular methods of detection and reported a predominance of PCV-13 serotypes within the cohort whereas this study revealed a predominance of NVT serotypes within the cohort. 24 The different findings between this study and that of Esposito et al (2016) could be due to regional variation and the lack of molecular detection methods used in this study. A factor that may be negatively impacting on the recovery of S. pneumoniae from the study volunteers could be the high rate of antibiotic use in this patient group; patients reported high antibiotic use between visits with the median number of courses of antibiotics prescribed in the period between visits ranging from one in the spring to two in the autumn.…”
Section: Discussioncontrasting
confidence: 76%
“…Table 2 lists examples of studies that attempted to define the rate of pneumococcal colonization in elderly persons (defined as either Ͼ60 or Ͼ65 years old in different studies) (15)(16)(17)(18)(19)(20)(21). Much of the variation between these studies can be explained by the different sampling sites-nasopharyngeal, oropharyngeal, or saliva-and detection methods-classical culture, PCR, or some combination of the two.…”
Section: Search Strategy We Searched Pubmed For (["Streptococcus Pneumentioning
confidence: 99%
“…[24][25][26][27] While this study evaluated the performance for S. pneumoniae detection by PCR in NP swab collected for viral studies, it was recognised that other specimen types, such as oral and oropharyngeal swabs, were previously shown to perform better than sampling from the nasopharynx to assess pneumococcal colonisation. [28][29][30] Since the performance of NP swab PCR is affected by the results of its comparator, a future studies would benefit from a direct comparison between PCR-based detection of pneumococcal DNA in NP swabs and concurrent quantitative S. pneumoniae from culture swabs collected from the nasopharynx. 31 Other studies have also suggested broth enrichment prior to lytA real-time PCR can enhance the detection of S. pneumoniae, particularly for low density colonisation.…”
Section: Open Accessmentioning
confidence: 99%